Application of fuzzy logic in drying: A review. Issue 5 (1st April 2022) - Hosseinpour, Soleiman; Martynenko, Alex
Abstract: This article presents a comprehensive review of almost all existing applications of fuzzy logic in drying technology to solve problems of nonlinear modeling, simulation, pattern recognition, clustering, classification, control, and optimization. The literature is categorized into three main streams: modeling, clustering/classification, and control. The benefits and shortcomings of fuzzy logic applications are systematically reviewed. Finally, a roadmap for the future studies based on the current state and significant underexplored potential of fuzzy logic in drying technology is proposed.